High moisture corn ensiled with urea - Heidker, J.; Bolsen, K.; Hinds, M.; Ilg, H.; Janicki, B.; Young, B. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
High moisture corn harvested at 18 and 26% moisture, rolled, treated with 0, .75, 1.5, or 2.25% urea (DM basis), and ensiled was evaluated for fermentation rate, chemical composition, and aerobic stability. Adding urea to 26% moisture corn increased the rate and extent of fermentation as measured by lactic, acetic, and total acid concentrations. Only a very limited fermentation occurred in the 18% moisture corn. No statistically significant differences were noted in DM loss or aerobic stability among the eight corn treatments.
Keywords: Beef; Corn; Urea; Fermentation